Creation of a sensor to measure strain of highly deformable solids - Serjouei, Ahmad (2009)
In recent years, industrial application of rubber components has been increased. One of the important issues in industry is strain measurement of soft materials. Health and usage monitoring of aerospace components in flight has been lately getting a lot of attention by aerospace companies. For instance, in the helicopter industry, efforts are underway to monitor vibration and stress levels, in real time, of most helicopter components made of metal and composites using accelerometers and metal foil strain gauges. On most helicopters and fixed wing airplanes, there are other flight critical components that are not made of metal and composites, but made of rubber such as rubber bearings, rubber lead-lag dampers and rubber engine mounts which also require stress monitoring. However, metal foil strain gauges cannot be used on the surface of these rubber components for strain measurement since rubber flexes too much and most strain gauges are incapable of handling such large strains. In many applications, the allowable deflection of the structure defines the safe operational limit; therefore, it is of great interest to have a structurally monitoring system capable of real time strain measurement. In fact, the purpose of continuously monitoring the distribution of strain in crucial structures is to better understand the behavior of the structure in extreme circumstances or otherwise anomalous conditions, whereby remedial action can be performed when required. A new sensor for measuring strain of highly deformable solids is proposed. This sensor is capable of measuring the strain of rubber or plastic component on which the sensor is bonded, in real time.